Elderly Health Gallery Training Through Healthy Gymnastics as an Effort to Improve the Quality of Life: Pelatihan Galeri Kesehatan Lansia Melalui Senam Sehat Sebagai Upaya Meningkatkan Kualitas Hidup - Ummul Khair Hasni; Ainun Afifah M.A.Machmud; Nur Fitri Annisa; Firmanto (PT. Lontara Digitech Indonesia, 2024)
The aging process affects various aspects of life, including health, economic and social. In the elderly, decreased muscle strength and body balance can increase the risk of falls and reduce quality of life. With the projected number of elderly continuing to increase, especially in developing countries like Indonesia, it is important to improve healthy lifestyles as an effort to improve the quality of life of the elderly. This research focuses on the implementation of a healthy exercise program in Taraweang Village, Labakkang District, Pangkajene Regency and South Sulawesi Islands, as part of community service activities. This program involves forming a cadre for the Elderly Health Gallery, providing health education, simple exercise training, and routine exercise activities. The results show an increase in elderly participation in routine exercise, with the number of participants increasing from 26 to 35 people during the implementation period. This healthy exercise has been proven to help improve body organ function, immunity and quality of life for the elderly, as well as providing social and mental benefits. This program is also expected to encourage understanding of the importance of routine health checks and physical activity in the elderly to improve their overall quality of life. Abstrak Proses penuaan mempengaruhi berbagai aspek kehidupan, termasuk kesehatan, ekonomi, dan sosial. Pada lansia, penurunan kekuatan otot dan keseimbangan tubuh dapat meningkatkan risiko jatuh dan menurunkan kualitas hidup. Dengan proyeksi jumlah lansia yang terus meningkat, terutama di negara berkembang seperti Indonesia, penting untuk memperbaiki gaya hidup sehat sebagai upaya meningkatkan kualitas hidup lansia. Penelitian ini berfokus pada implementasi program senam sehat di Desa Taraweang, Kecamatan Labakkang, Kabupaten Pangkajene dan Kepulauan Sulawesi Selatan, sebagai bagian dari kegiatan pengabdian masyarakat. Program ini melibatkan pembentukan kader Galeri Kesehatan Lansia, penyampaian edukasi kesehatan, pelatihan senam sederhana, dan kegiatan senam rutin. Hasil menunjukkan adanya peningkatan partisipasi lansia dalam senam rutin, dengan jumlah peserta meningkat dari 26 hingga 35 orang dalam periode pelaksanaan. Senam sehat ini terbukti membantu meningkatkan fungsi organ tubuh, imunitas, dan kualitas hidup lansia, serta memberikan manfaat sosial dan mental. Program ini juga diharapkan dapat mendorong pemahaman pentingnya pemeriksaan kesehatan rutin dan aktivitas fisik pada lansia untuk memperbaiki kualitas hidup mereka secara keseluruhan.